Targeting insulin-degrading enzyme to treat type 2 diabetes - Tang, Wei-Jen (Trends Endocrinol Metab, 2015)
Insulin degrading enzyme (IDE) selectively degrades peptides such as insulin, amylin, and amyloid β (Aβ) that form toxic aggregates, to maintain proteostasis. IDE defects are linked to the development of type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD). Structural and biochemical analyses revealed the molecular basis for IDE-mediated destruction of amyloidogenic peptides and this information has been exploited to develop promising inhibitors of IDE to improve glucose homeostasis. However, the inhibition of IDE can also lead to glucose intolerance. This review focuses on recent advances regarding our understanding of the structure and function of IDE and the discovery of IDE inhibitor, as well as challenges in developing IDE-based therapy for human diseases, particularly T2DM.